Environmental and management determinants of vegetation state on protected areas in the eastern Lowveld of South Africa - Peel, M. J. S.; Kruger, J. M.; Zacharias, P. J. K. (African journal of ecology, 2005)
Principal driving determinants (rainfall, geology, soil, tree density and canopy cover, animal numbers and feeding classes, and fire) of vegetation structure and function in the Lowveld savanna in South Africa were grouped for a 7‐year period to establish their influence on the limiting herbaceous layer. Grass type, abundance and cover were examined (450 sites; approximately 4000 km2). Using ordination, the variation and differences in the herbaceous‐response variables viz. perennial composition and cover allowed for the broad environmental grouping of areas of similar ecological potential. We demonstrate that areas of higher ecological potential carried higher densities of large herbivores without detrimentally affecting herbaceous composition and cover. The results have implications for land users and policy makers in terms of setting animal stocking density guidelines. Résumé Les principaux déterminants moteurs (précipitation, géologie, sol, densité d'arbres et couverture de la voûte; nombre d'animaux et classes alimentaires; incendie) de la structure et fonction de la végétation dans la savane de Lowveld en Afrique du Sud furent réunis pendant sept ans dans le bût d’établir l‘étendue de leur impacte sur la couche herbacée restrictive. La classe de l'herbe, l'abondance et couverture furent examinées (450 zones; ∼4000 km2). En se servant de l'ordination, la variation et les différences dans les variables de réponse‐herbacée vis‐à‐vis de la composition pérenne et la couverture a permis un regroupement environnemental général des zones avec un potentiel écologique semblable. Nous montrons ici que les zones de fort potentiel écologique supportent des plus fortes densités de grands carnivores, sans pour autant nuire à la composition de l'herbe et couverture. Les résultats ont des implications pour les utilisateurs de la terre et les responsables politiques par rapport à la création d'une directive sur l'approvisionnement d'animaux.